Characteristics of Music Culture Lessons - qizi, Rustamjonova Dilkhavas Ravshvnbek (International Journal on Integrated Education, 2023)
In the course of the articles music culture lessons, music in the course of independent lesson activities, artistic study and performance literacy of musical works, composition of high and low relationships of musical sounds, literacy analysis of works related to singing and listening to oral methods of teaching tasks and music lessons based on the impressions students receive from everyday life and musical experience.